Evolusi Inovasi Industri Maritim Berkelanjutan dalam Mendorong Pertumbuhan Ekonomi Pesisir Indonesia di Era Blue Economy - Greciani Greciani (Universitas Teuku Umar, 2026)
Indonesia as the world’s largest archipelagic country has significant potential in developing the maritime industry as a primary driver of national economic growth. The transformation of the maritime industry in the blue economy era requires integration among technological innovation, environmental sustainability, and coastal community empowerment. This study aims to analyze the evolution of sustainable maritime industrial innovation and its impact on Indonesia’s coastal economic growth. This research employed a qualitative method using a systematic literature review approach from national and international journals, policy reports, and secondary data related to maritime industries. The findings reveal that maritime industrial innovation has shifted from resource exploitation approaches toward blue economy systems emphasizing production efficiency, logistics digitalization, smart port development, renewable marine energy, and modern fisheries industrialization. These innovations contribute to improved economic productivity, employment expansion, and enhanced competitiveness of coastal regions. However, challenges such as limited infrastructure, technological disparities, ecosystem degradation, and weak human resource capacity remain major barriers. Therefore, collaborative policies involving government, private sector, academia, and communities are essential to realize an inclusive and sustainable maritime industry.